The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1017/s0033291712002279
|View full text |Cite
|
Sign up to set email alerts
|

Increased stress reactivity: a mechanism specifically associated with the positive symptoms of psychotic disorder

Abstract: Patients with a 'psychotic syndrome' with high levels of positive symptoms and low levels of negative symptoms show increased reactivity to stress in daily life, indicating that stress reactivity is a possible risk factor underlying this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 80 publications
5
72
1
Order By: Relevance
“…These observations support the concept of a causal, dose-response relationship between victimisation and the risk and severity of psychotic symptoms (Bebbington et al, 2013, Lataster et al, 2013, although in the present study prolonged bullying was not associated with an increased level of paranoid ideation. Future work could investigate any cumulative effect of other forms of victimisation and adversity and the tendency for paranoid ideation in the VR environment, as well as the relation between adverse experiences and neurobiological abnormalities in the emergence of psychotic symptoms.…”
Section: Increased Prevalence Of Bullying In People At High Risk For supporting
confidence: 87%
“…These observations support the concept of a causal, dose-response relationship between victimisation and the risk and severity of psychotic symptoms (Bebbington et al, 2013, Lataster et al, 2013, although in the present study prolonged bullying was not associated with an increased level of paranoid ideation. Future work could investigate any cumulative effect of other forms of victimisation and adversity and the tendency for paranoid ideation in the VR environment, as well as the relation between adverse experiences and neurobiological abnormalities in the emergence of psychotic symptoms.…”
Section: Increased Prevalence Of Bullying In People At High Risk For supporting
confidence: 87%
“…Previous research has shown a link between stress reactivity and momentary increases in positive symptoms when exposed to daily stressor (Myin-Germeys et al, 2005), which was specifically related to positive psychotic symptoms (Lataster et al, 2013). Further work exploring the interplay between these factors (social defeat, baseline positive symptoms, and 'in the moment' paranoid ideation during the VR), would allow a better understanding of the elements that are critical to the processes underlying the experience of people at UHR in the VR environment.…”
Section: Discussionmentioning
confidence: 95%
“…Recent research has also demonstrated a relationship of higher perceived stress with depression and positive symptoms in both at-risk samples (Pruessner et al, 2011, Tessner et al, 2011, Palmier-Claus et al, 2012, Devylder et al, 2013, Cullen et al, 2014a and first episode psychosis patients (Raune et al, 2006, Lataster et al, 2013. However, as noted above, elevated stress levels may be secondary to illness related factors, rather than causal.…”
Section: Stress Exposure Perceived Stress and Early Life Adversitymentioning
confidence: 93%